Злочин і покарання в релігійній доктрині християнства - Крисюк, Ю.; Krysiuk, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається відображення проблеми злочину та покарання в релігійній доктрині християнства та вплив релігійних норм на становлення й розвиток кримінального законодавства України, оскільки саме християнська релігія, будучи морально-нормативною системою, відіграла надважливу роль при формуванні і реалізації правових норм, в тому числі й кримінальних. The article considers the reflection of the issues of crime andpunishment in the religious doctrine of Christianity and religious norms impact on the formation and development of criminal law in Ukraine. The researchers ofthe Bible argue that this Holy Book, along with religious-philosophical and moral-ethical principles, naturally contains legal codes and other legal norms. The author singles out the principal norms among those that are crucial for the criminal and criminal-procedural legislation: the equality of people before the court, the presence of witnesses in court while hearing a criminal case, the duty of all participants of process to give truthful testimony and many others. With regard to the specific groups of crimes the researchers acknowledge that even the Pentateuch of Moses mentioned crimes against religion, against life and health, against the will of man, against morality, marriageand family, against property. This suggests that the Bible is the source of the current criminal law. The author draws the conclusion that knowledge of the legal provisions can not occur in isolation, without taking into account the conditions of historical development.
Crime and Punishment in the Religious Doctrine of Christianity
Keywords: злочин; покарання; християнство; релігійна доктрина; кримінальне законодавство; crime; punishment; religious doctrine; criminal responsibility